Qualitative Analysis of Aflatoxin from Aspergillus flavus isolates - D.P. Gadgile, R.B. Kakde, R.S. Gaikwad, A.D. Hatti, P.P. Pangrikar, A.M. Chavan (Recent Research in Science and Technology, 2009)
Different isolates of Aspergillus flavus were isolated from five varieties of groundnut. These isolates were grown on liquid SMKY medium. By using TLC the cultural filtrate produced by these isolates were screened for Aflatoxin production. About 80% of A. flavus isolates were found to produce aflatoxin, out which 100% isolates produces aflatoxin (B1), 30% isolates produces B1 and B2, 10% isolates produces B1 and G1 aflatoxin.